Lamb feeding experiments - Menzies, C.S.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
Delivery of 601 finewool. Wether feeder lambs was accepted at Menard, Texas, October 8, 1964. Average weight was 68.9 pounds; cost, $19.25 per cwt. Lambs were shorn (average fleece weight, 3.2 lbs.) and shipped 543 miles to Garden City on a triple-deck truck. They arrived October 9, a.m., weighing an average of 60.4 pounds. They were divided into groups of about 50 lambs and fed a ration of medium-quality alfalfa hay and chopped sorghum stubble until started on test.
Keywords: Lamb; Implant; Gain; High-concentrate ration